Farm management and husbandry practices associated with spontaneous humeral fractures in New Zealand dairy heifers. - Wehrle-Martinez A; Lawrence KE; Back PJ; Rogers CW; Dittmer KE (Taylor and Francis Group, 2024)
AIMS: To use a farm-based survey to identify characteristics of the New Zealand dairy system associated with the risk of spontaneous humeral fracture in dairy heifers. METHODS: A questionnaire was designed and made available in print and online to collect information from dairy farmers and/or veterinarians, across New Zealand, about the management and nutrition of cows from birth to first lactation. Data were collected from July 2019 to March 2020 from farms that either had recorded (case farms) or not recorded (control farms) cases of humeral fractures in dairy heifers. RESULTS: A total of 68 completed questionnaires were returned, with 35 responses from case farms and 33 responses from control farms. Twenty-six responses (38%) were from the South Island (13 case farms and 13 control farms) and 38 responses (56%) were from the North Island (20 case farms and 18 control farms). For four questionnaires (6%) farm location was not given. Adjusting for the effect of age when calves accessed pasture, case farms had increased odds of having Holstein-Friesian Jersey crossbreed cows as the predominant breed (OR = 9.7; 95% CI = 3.1-36.0; p < 0.001). Adjusting for the effect of breed, allowing calves access to pasture a week later decreased the odds of being a case farm (OR = 0.68; 95% CI = 0.47-0.90; p = 0.006). CONCLUSIONS: Cows being Holstein-Friesian Jersey crossbreed was identified as a possible risk factor associated with spontaneous humeral fracture in dairy heifers in New Zealand. Given the small sample size, the likely multifactorial aetiology for humeral fractures, and the non-randomised survey, this risk factor, and the possible association between age at turn out and herd production with humeral fractures, all require further investigation.
Keywords: Holstein-Friesian Jersey; Humeral fractures; case control study; heifers; survey; Animals; Cattle; Female; Farms; New Zealand; Lactation; Risk Factors; Dairying; Humeral Fractures; Cattle Diseases